1995
DOI: 10.1177/0013164495055006011
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the Quick Discrimination Index (QDI)

Abstract: A series of empirical studies was conducted to develop and validate the Quick Discrimination Index (QDI), a 30-item, Likert-type self-report inventory. The QDI measures attitudes toward racial diversity (multiculturalism) and women's equality and is appropriate for late adolescents and adults. The instrument has applicability across racial/ethnic groups. Exploratory factor analyses examining both orthogonal and oblique rotations indicate that the QDI is best conceptualized as a tridimensional measure of attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
177
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(189 citation statements)
references
References 8 publications
11
177
0
1
Order By: Relevance
“…For the present study, a coefficient alpha of.88 was obtained for the sample. The COBRAS demonstrates moderate to strong correlations with two measures of racial discrimination (i.e., Modern Racism Scale; McConahay, 1986; Quick Discrimination Index; Ponterotto et al, 1995), providing evidence of concurrent validity evidence. Both an initial exploratory factor analysis and a confirmatory factor analysis provided evidence of construct validity, and a low, insignificant correlation with the MCSDS (Crowne & Marlowe, 1960;Reynolds, 1982) provides evidence of discriminant validity.…”
mentioning
confidence: 96%
“…For the present study, a coefficient alpha of.88 was obtained for the sample. The COBRAS demonstrates moderate to strong correlations with two measures of racial discrimination (i.e., Modern Racism Scale; McConahay, 1986; Quick Discrimination Index; Ponterotto et al, 1995), providing evidence of concurrent validity evidence. Both an initial exploratory factor analysis and a confirmatory factor analysis provided evidence of construct validity, and a low, insignificant correlation with the MCSDS (Crowne & Marlowe, 1960;Reynolds, 1982) provides evidence of discriminant validity.…”
mentioning
confidence: 96%
“…Previous studies have demonstrated that the QDI has excellent psychometric properties (Ponterotto et al, 1995). The 16-item GTSE (e.g., "When I really try, I can get through to the most difficult students") and the 10-item CTSE (e.g., "I have the knowledge and skills to be sensitive to the needs and preferences of culturally diverse students") were developed for the present study based on Bandura's (1977) recommendation for constructing self-efficacy measures.…”
Section: Methodsmentioning
confidence: 99%
“…Several measures of perceived discrimination have been developed and used in research. Examples of these are the Experiences of Discrimination (EOD) (Krieger, Smith, Naishadham, Hartman & Barbeau, 2005), the Schedule of Sexist Events (SSE) (Klonoff & Landrine, 1995) and the Quick Discrimination Index (QDI) (Ponterotto et al, 1995). In the EOD (Krieger et al, 2005) participants are asked a general question about experiences of discrimination, after which the focus moves to the types of discrimination (sex, country of birth, social class, sexual orientation, religion) suffered by participants, and where they occurred (at work, getting a job, discrimination at home by his or her partner, discrimination at home by others, when receiving medical care or being on the street or in a public setting).…”
Section: The Measurement Of Gender Equitymentioning
confidence: 99%